Contextual PAI Learning Design: Integration of Contextual Teaching and Learning with Islamic Epistemology in the Society 5.0 Era - Faqih Abdul Aziz; Mita Nur Khasanah; Yaniz Naura Naviana Haryadi; Ali Mudlofir; Ali Mas'ud; Asep Saepul Hamdani (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The Era of Society 5.0 places Islamic Religious Education (PAI) at a critical intersection between the necessity of pedagogical adaptation and the obligation to maintain transcendental integrity. The Contextual Teaching and Learning (CTL) approach, which is derived from Western pragmatism epistemology, has proven to have an ontological deficit because it negates the transcendental dimension as the main axis of religious education. On the other hand, there is currently no instructional syntax that comprehensively deconstructs secular CTL and reconstructs it based on Islamic Epistemology to address the challenges of Society 5.0 disruption. Objective: This research aims to (1) analyze the epistemological limitations of Western CTL thru the perspective of Islamic Epistemology, and (2) formulate an instructional syntax for contextual PAI learning design that operationally integrates the pillars of CTL with evidence from the Qur'an and Hadith. Method: This qualitative research based on library research applies the Conceptual Framework Analysis approach integrated with qualitative content analysis. Data was extracted from authoritative texts of the Qur'an, Hadith, tafsir books, and globally reputable journal literature (Scopus and Web of Science), verified thru source triangulation. Results: This research produces: (1) An Epistemological Deconstruction Matrix that maps the limitations of the seven pillars of secular CTL and the Islamic foundation as its alternative; and (2) A Contextual PAI Instructional Design in the form of a continuous seven-phase syntax cycle: Bina' Ma'rifah, Istiqra’ wa Tadabbur, Sual wa Jawab, Majelis Ilmi wa Syura, Uswah Hasanah, Muhasabah, and Mizanul Amal. This design has proven to realize the eight dimensions of the graduate profile of the Merdeka Curriculum and acts as a proactive mitigation instrument against moral crises and digital radicalism. The novelty of this study lies in the formulation of a closed-loop instructional system that is adaptive to the disruptions of Society 5.0 civilization with a comprehensive eschatological accountability.